Correlation of serum parameters with disease severity, exacerbations and hospitalizations in patients with Non-cystic fibrosis bronchiectasis - Kallarakal, John Sonia; A., Fathahudeen; Mallan, K. G. R.; D., Manjula V. (International Journal of Research in Medical Sciences, 2019)
Background: The factors essential to define the severity and the prognosis of subjects with NCFB have not been sufficiently assessed. A prospective observational study was conducted to assess the serum parameters, their correlation with BSI (bronchiectasis severity index) and FACED (FEV1% predicted, age, chronic colonization by pseudomonas aeruginosa, extension by radiological assessment and dyspnoea) score in assessing disease severity and respiratory hospitalizations in patients with NCFB. Methods: About 76 clinically stable patients diagnosed as NCFB were included. Data extraction was done using structured proforma. The BSI and FACED scores were calculated. The serum parameters albumin, CRP (C-reactive protein), ANC (Absolute neutrophil count) and Hb (hemoglobin) levels were estimated. The number of exacerbations and hospitalizations during the 6 months follow up period were recorded. Results: The mean value of the serum parameters albumin, CRP, absolute neutrophil count (ANC) and Hb were 3.86 (95% CI 3.77- 3.95), 19.61 (95% CI 15.53 -23.68), 8632.95 (95% CI 7258.5-10068) and 12.3 (95% CI 11.84- 12.74) respectively. There was strong negative correlation between serum albumin and the BSI and FACED score. The mean exacerbations and hospitalizations during the 6 months follow up period were 3.3 (95% CI 2.93-3.65) and 1.14 (95% CI 0.85-1.44) respectively. Conclusions: The serum albumin level exhibited strong correlation and was identified as a variable associated with the BSI and FACED scores. Further studies in this direction are needed for use of serum parameters in severity assessment.